ANALISIS MODAL SOSIAL PADA HIMPUNAN PELAJAR MAHASISWA PELALAWAN (HIPMAWAN) DI PEKANBARU - Mhd. Ihsanullah; Hesti Asriwandari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This study discusses the social capital within the Association of Students Pelalawan (HIPMAWAN) Pekanbaru. Social capital within the Association of Students Pelalawan (HIPMAWAN) Pekanbaru can be seen through some of the indicators of which is the notion of social capital, social capital within an organization, the elements of social capital, social interaction and social networks. The subjects were students who are members of the Association of Students Pelalawan (HIPMAWAN) Pekanbaru. The method used in this research is purposive sampling and analysis of the data used is descriptive and qualitative analysis. Data collected by using interviews and documentation. The theory used is the theory of social capital. This study aims to determine what kind of social capital and what activities are carried out by the Association of Students Pelalawan (HIPMAWAN) Pekanbaru. Results of this study is the social capital that exist within HIPMAWAN is based on the equation, namely the area of origin of students Pelalawan and all activities undertaken by HIPMAWAN is based for the progress and welfare of society and Pelalawan.Keywords: Social Capital, HIPMAWAN